The development department's Aidilfitri celebration - UiTM, UGC (UiTM Green Centre, 2025)
On 25 April 2025, the development department's Aidilfitri celebration, “Syawal at the multilevel parking lot,” was held at Dewan Agung Tuanku Canselor (DATC), UiTM Shah Alam. Thank you to the development department staff who assisted in serving food at their respective division booths, helping to enliven the celebration and foster camaraderie in conjunction with the joyous month of Shawal.